Modified cellulose adhesive and preparation method thereof
Through the collaborative design of components such as modified cellulose-based emulsion, VAE composite emulsion and rosin emulsion, the shortcomings of cellulose adhesive in terms of interface adhesion, water resistance and stability are solved, and high strength and water resistance are improved.
Patent Information
- Application Number
- CN202511054423.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-30
- Publication Date
- 2025-08-29
- Estimated Expiration
- 2045-07-30
AI Technical Summary
Existing cellulose adhesives have shortcomings in insufficient interface adhesion, poor water resistance and stability defects, and conventional modification methods cannot fundamentally break through the performance bottleneck.
Through the collaborative design of multiple active sites, an anti-hydrolysis barrier and dual toughening mechanism is built, and components such as modified cellulose-based emulsion, VAE composite emulsion, rosin emulsion and crosslinking agent are used to form a chain structure and hydrophobic barrier that is both rigid and flexible, enhancing bond strength and water resistance.
It significantly improves the bonding strength and water resistance of the modified cellulose adhesive, extends the life of the adhesive, and improves its stability in high temperature and high humidity environments.
Smart Images

Figure CN120554989A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of chemical modification of natural polymer materials, and particularly relates to a modified cellulose adhesive and a preparation method thereof. Background Art
[0002] As a natural polymer material, cellulose has the advantages of being renewable and biocompatible in the field of adhesives. However, due to its structural limitations, it also has the following core problems: 1. Insufficient interfacial adhesion: The hydrogen bonds between natural cellulose molecular chains are weak, resulting in low interfacial bonding strength; 2. Poor water resistance: A large number of hydrophilic hydroxyl groups absorb water and swell, weakening the bonding strength; 3. Stability defects: Depolymerization is prone to occur under high temperature or high humidity environments.
[0003] At present, conventional modification methods cannot fundamentally break through the performance bottleneck. For example, the physical blending method only enhances viscosity by blending thickeners, but cannot improve interfacial bonding strength, and phase separation leads to stratification; simple etherification or esterification only modifies a single functional group, and the active sites of the molecular chain are not fully utilized; there is a lack of a thermally stable skeleton, and the high-temperature interface is prone to failure. Summary of the Invention
[0004] In order to overcome the above-mentioned deficiencies of the prior art, the present invention provides a modified cellulose adhesive and a preparation method thereof, which achieves targeted performance improvement through molecular design, including the coordinated design of multiple active sites, the construction of an anti-hydrolysis barrier and a dual toughening mechanism.
[0005] The technical solutions for achieving the purpose of the present invention are as follows: A modified cellulose adhesive is compounded from multiple raw materials and includes the following components, by weight: 50-70 parts of a modified cellulose-based emulsion, 10-20 parts of a VAE composite emulsion, 5-8 parts of a rosin water emulsion, 3-8 parts of a crosslinking agent, and 2-5 parts of a plasticizer. The modified cellulose-based emulsion is obtained by mixing cellulose and modified cellulose in a certain proportion; the modified cellulose is obtained by grafting a nanocellulose solution with an epoxy hypophosphite compound and a fluorine-containing pentaphenyl alkynyl dicarboxylic acid compound; the structure of the modified cellulose is shown in Formula 1: , formula 1.
[0006] Preferably, the VAE composite emulsion is composed of two VAE emulsions with different glass transition temperatures, wherein the glass transition temperature of one VAE emulsion is lower than 0°C, and the glass transition temperature of the other VAE emulsion is higher than or equal to 0°C; the mass ratio of the two emulsions is (0.45~0.55):(0.45~0.55); the crosslinking agent is trimethylolpropane triglycidyl ether; and the plasticizer is dipropylene glycol dibenzoate.
[0007] Preferably, the VAE emulsion with a glass transition temperature lower than 0°C is VAE920 emulsion produced by Wacker, Germany, and the VAE emulsion with a glass transition temperature higher than or equal to 0°C is DA102 VAE emulsion produced by Dalian Chemical in Taiwan, China; further preferably, the mass of the VAE920 emulsion is 45% of the mass of the total emulsion.
[0008] The gradient stirring was as follows: a stirring speed of 80 rpm for 0-2 min, a stirring speed of 120 rpm for 3-5 min, and a stirring speed of 150 rpm for 6-10 min.
[0009] The preparation method of the modified cellulose comprises the following steps: S1. Dissolve 2.5 eq of furan and 1 eq of 1-aminomethylmaleimide hydrochloride in toluene. Heat the mixture to 90°C and reflux for 17–20 h using a Dean-Stark apparatus. After the reaction, remove the solvent under reduced pressure. Purify the crude product by silica gel column chromatography to obtain the amino Diels–Alder addition product, whose structure is shown below: ; S2. Under a nitrogen atmosphere, dissolve 1.0 eq of the product from step S1 and 1.2 eq of an epoxy hypophosphite compound in tetrahydrofuran, heat to 60°C, and stir for 20-24 h. After the reaction, remove the solvent by distillation under reduced pressure. Purify the mixture by silica gel column chromatography to obtain the hypophosphite-esterified amino Diels-Alder addition product, the structure of which is shown below: ; S3. Dissolve 1.1-1.3 eq of a fluorine-containing pentaphenylalkynyl dicarboxylic acid compound in anhydrous dichloromethane, cool to 0°C in an ice bath, add 1.2 eq of dicyclohexylcarbodiimide sequentially, stir for 10 min, then add 0.1 eq of 4-dimethylaminopyridine, and finally add dropwise a 0.1 mol / L solution of 1 eq of a hypophosphite-esterified amino Diels-Alder addition product in anhydrous dichloromethane. Remove the ice bath, stir at room temperature for 15-20 h, filter after completion of the reaction, and wash the filtrate sequentially with a 5% (mass fraction) aqueous solution of citric acid, a saturated sodium bicarbonate solution, and brine, then dry over anhydrous sodium sulfate. Purify by silica gel column chromatography to obtain a hypophosphite monomer having the structure shown below: ; S4. Synthesis of polyphosphite: Under nitrogen atmosphere, dissolve 1 eq of the phosphite monomer obtained in step S3 and 1 / 200-1 / 50 eq of the catalyst in toluene for ring-opening metathesis polymerization. Heat to 50-90°C for 3-5 h, then quench the reaction by adding vinyl ethyl ether. Remove the solvent, and recrystallize from acetone to obtain polyphosphite. S5. Epoxidation of polyphosphite: Under a nitrogen atmosphere, the polyphosphite obtained in step S4 was dissolved in toluene, and m-chloroperbenzoic acid was added and stirred at 10-25 °C for 2-5 h. Excess methanol was added to precipitate the epoxidized polyphosphite; S6. Cellulose modification: The nanocellulose aqueous suspension was diluted to a solution with a solid content of 0.5% by weight, and a 0.5 mol / L MgCl2 aqueous solution was added relative to 1.2 eq of nanocellulose, and stirred at room temperature for 30 min; epoxidized polyphosphite was added, and the mass ratio of nanocellulose solid content to epoxidized polyphosphite was (3~9):1. After stirring at 600~800 rpm at 25~40°C for 8~12 h, ultrasonic dispersion was continued for 10~30 min, and disodium ethylenediaminetetraacetic acid solution was added and stirred for 20 min; after standing at room temperature to remove bubbles, the solution was placed in liquid nitrogen and frozen for 5~10 min. The frozen sample was placed in a freeze dryer at a temperature of -60~-50°C and a pressure of 1~20 Pa and freeze-dried for 60~72 h to obtain a gel-like solid. The obtained gel was placed in a vacuum drying oven at a temperature of 110~120°C for 5~10 min to obtain hypophosphite-modified cellulose.
[0010] By adopting ring-opening metathesis polymerization, polyphosphates of different molecular weights can be simply and efficiently obtained by changing the ratio of phosphate monomer to catalyst. The catalyst is one or more of Grubbs' first-generation catalyst, Grubbs' second-generation catalyst, and Grubbs' third-generation catalyst. The molar ratio of phosphate monomer to catalyst is (50-200):1.
[0011] Preferably, the catalyst is a Grubbs II catalyst.
[0012] The preparation method of the fluorine-containing pentaphenyl alkynyl dicarboxylic acid compound comprises the following steps: (1) 2.5 eq of 4-fluorobenzyl bromide, 1 eq of 2,5-diiodobenzene-1,4-diol, and 0.25 eq of 18-crown-6 were mixed in anhydrous acetone, 5-6 eq of potassium carbonate were added, and the mixture was degassed with nitrogen. The mixture was stirred and heated to 60°C for 18-20 h. After the reaction, the hot mixture was filtered and recrystallized from acetone to obtain 2,5-diiodobis(4-fluorobenzyloxy)benzene, the structure of which is shown below: ; (2) 1 eq of 2,5-diiodobis(4-fluorobenzyloxy)benzene, 4 eq of methyl 4-ethynylbenzoate, 0.3 eq of cuprous iodide, and 0.1 eq of bis(triphenylphosphine)palladium(II) dichloride were mixed, the mixture was degassed with nitrogen, anhydrous tetrahydrofuran and anhydrous triethylamine were added, and the mixture was stirred in the dark under a nitrogen atmosphere for 18 to 20 h. After the reaction was completed, the mixture was cooled to room temperature and poured into water. The mixture was purified by silica gel column chromatography to obtain 2,5-bis(4-fluorobenzyloxy)-1,4-bis(4-methylphenylethynyl)benzene, the structure of which is shown below: ; (3) 1 eq of 2,5-bis(4-fluorobenzyloxy)-1,4-bis(4-methylphenylethynyl)benzene was dissolved in 15 mL of tetrahydrofuran, 250 eq of potassium hydroxide was dissolved in 8 mL of methanol and added to the mixed solution, and stirred at room temperature for 20-22 h; the reaction mixture was acidified with 120 mL of 2 mol / L trifluoroacetic acid tetrahydrofuran solution, stirred at room temperature for 1 h, and then poured into water. The precipitate was filtered and washed with water. The crude product was treated with boiling water and ultrasonically shaken to remove inorganic salt impurities. The solid was dried and recrystallized in chloroform to obtain a fluorine-containing pentaphenyl alkynyl dicarboxylic acid compound, as shown in structural formula 2: , formula 2.
[0013] The preparation method of the epoxy hypophosphite compound comprises the following steps: (1) In air, 6 eq of sodium hypophosphite monohydrate, 1 eq of propynyl glycidyl ether, and 1 eq of triethylborane solution were mixed in a solution with a volume ratio of methanol to dioxane of 5:1; the solution was stirred in air at room temperature for 4 h. After the reaction was completed, the precipitate was filtered and washed three times with cold methanol. After drying over phosphorus pentoxide in a vacuum, the intermediate sodium phosphate salt had the structure shown below: ; (2) Under nitrogen atmosphere, 1 eq of sodium phosphate intermediate, 2.2-2.5 eq of bromoalkane and 0.05-0.10 eq of tetrabutylammonium bromide were mixed with anhydrous acetonitrile, stirred and heated to 80-90°C, and reacted for 24 h. After the reaction, the mixture was cooled to room temperature and the solvent was removed under reduced pressure. The residue was extracted with ethyl acetate and saturated brine. The organic phases were combined, dried over anhydrous sodium sulfate solid, and purified by silica gel column chromatography to obtain an epoxy hypophosphite compound, the structure of which is shown in Formula 3: , formula 3.
[0014] Preferably, the brominated alkane includes one or more of 1-bromopentane, 1-bromohexane, 1-bromoheptane, 1-bromooctane, 1-bromononane, 1-bromodecane, 1-bromodencane, 1-bromodencane, 1-bromodencane, 1-bromodencane, 1-bromodencane, 1-bromodencane, 1-bromodencane, 1-bromodencane, 1-bromodencane, 1-bromodencane, 1-bromodencane.
[0015] The present invention also protects a method for preparing the modified cellulose adhesive, comprising the following steps: (1) Preparation of modified cellulose-based emulsion: cellulose and modified cellulose were mixed in a mixed solvent at a mass ratio of (1-8):1, heated to 60-65 °C, stirred at 1200-1500 rpm, and dissolved under ultrasonic-assisted treatment for 30-40 min; (2) Preparation of rosin water emulsion: solid rosin resin is added to boiling water, surfactant is gradually added, stirred at 800 rpm for 20 min, cooled to 60°C to obtain rosin water emulsion, and sieved through a 200 mesh sieve to remove undispersed particles; the mass ratio of rosin to water is 1: (5-8); the mass ratio of rosin to surfactant is (10-15): 1; the surfactant is an anionic surfactant, preferably sodium lauryl sulfate; (3) Preparation of VAE composite emulsion: two VAE emulsions were mixed at 40 °C, 0.3% of silicone defoamer was added, and the mixture was stirred at 200 rpm for 15 min to obtain a VAE composite emulsion; (4) Cross-linking agent and plasticizer treatment: dilute the cross-linking agent with an equal volume of ethanol; preheat the plasticizer to 50°C; (5) Preparation of modified cellulose adhesive: The reactor was preheated to 45 °C in a dark environment, and the modified cellulose-based emulsion and VAE composite emulsion were added and stirred in a gradient manner for 10 min. Then, the rosin water emulsion was added and stirred for 5 min. The pretreated plasticizer was slowly added within 5 min, and the diluted cross-linking agent was slowly added dropwise within 10 min. The temperature was maintained at 45 °C, and the mixture was stirred at 150 rpm for 10-15 min. The mixture was vacuum degassed for 20 min, and the pH was adjusted to 7 with ammonia water. The mixture was filtered through 0.5 μm precision to obtain the modified cellulose adhesive.
[0016] The mixed solvent is a mixed solvent with a volume ratio of water to NMP of 7:3; the ultrasonic auxiliary parameters are set to 40 kHz and 600 W.
[0017] Beneficial effects The present invention has the following beneficial effects: The present invention provides a modified cellulose adhesive and a preparation method thereof, which achieves targeted performance improvement through molecular design of cellulose: 1. Collaborative design of multiple active sites: A "rigid and flexible" chain structure is constructed. Rigid fluorinated aromatic rings inhibit molecular chain slippage at high temperatures, while long-chain alkane ester groups are used to enhance the hydrophobic interface and form a hydrophobic barrier. The fluorinated alkynyl conjugated system enhances van der Waals forces through electron cloud density, helps resist UV degradation, and helps extend the life of the adhesive. Phosphate groups form multiple hydrogen bonds and metal chelation with cellulose hydroxyl groups, synergistically improving the bond strength and water resistance of the modified cellulose adhesive. 2. Build an anti-hydrolysis barrier: The ether bond is good at resisting acid and alkali attacks, and the imide bond design is more stable than the ordinary amide bond. The two synergistically form an anti-hydrolysis barrier; 3. Dual Toughening Mechanism: The combination of ether bonds and alkyl chains helps enhance the molecule's elongation at break and impact resistance. Furthermore, by combining with VAE composite emulsions and rosin water emulsions, the initial viscosity is increased. The hydrophobic fluorine in the modified cellulose synergistically reduces alternating surface tension, accelerating adhesive wetting and improving spreading uniformity. Rosin resin fills the pores between cellulose molecules, enhancing adhesive cohesion and shear strength. The VAE composite emulsion wraps the cellulose chains, addressing cellulose's brittleness and high shrinkage. The fluorine atoms in the modified cellulose synergize with the VAE film barrier to prevent moisture erosion, ensuring the long-term resistance of the modified cellulose adhesive to mildew and debonding. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is a synthetic step for modified cellulose.
[0019] Figure 2 This is the H NMR spectrum of modified cellulose 1. DETAILED DESCRIPTION
[0020] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative efforts shall fall within the scope of protection of the present invention.
[0021] In the examples, the experimental methods used are conventional methods unless otherwise specified, and the materials, reagents, etc. used are all commercially available unless otherwise specified.
[0022] The raw materials and equipment used in the embodiments and comparative examples are described below: Epoxy hypophosphite compound 1: Homemade, preparation method is as follows: (1) In air, 6 eq of sodium hypophosphite monohydrate, 1 eq of propynyl glycidyl ether, and 1 eq of triethylborane solution were mixed in a solution with a volume ratio of methanol to dioxane of 5:1; the solution was stirred in air at room temperature for 4 h. After the reaction was completed, the precipitate was filtered and washed three times with cold methanol. After drying over phosphorus pentoxide in a vacuum, the intermediate sodium phosphate salt had the structure shown below: ; (2) Under nitrogen atmosphere, 1 eq of sodium phosphate intermediate, 2.2-2.5 eq of 1-bromohexadecane and 0.05-0.10 eq of tetrabutylammonium bromide were mixed with anhydrous acetonitrile, stirred and heated to 80-90°C, and reacted for 24 h. After the reaction, the mixture was cooled to room temperature and the solvent was removed under reduced pressure. The residue was extracted with ethyl acetate and saturated brine. The organic phases were combined, dried over anhydrous sodium sulfate solid, and purified by silica gel column chromatography to obtain epoxy hypophosphite compound 1, the structure of which is shown below: ; Epoxy hypophosphite compound 2: homemade. The preparation method is similar to that of epoxy hypophosphite compound 1, except that 1-bromohexadecane added in step (2) is replaced with 1-bromopentane. Other conditions remain unchanged, and epoxy hypophosphite compound 2 is obtained. The structure is shown in the following formula: ; Epoxy compound 3: n-butyl glycidyl ether, product number B829911, purchased from Shanghai MacLean Biochemical Technology Co., Ltd., with the structure shown below: ; Fluorine-containing pentaphenyl alkynyl dicarboxylic acid compound 1: homemade, the preparation method is as follows: (1) 2.5 eq of 4-fluorobenzyl bromide, 1 eq of 2,5-diiodobenzene-1,4-diol, and 0.25 eq of 18-crown-6 were mixed in anhydrous acetone, 5-6 eq of potassium carbonate were added, and the mixture was degassed with nitrogen. The mixture was stirred and heated to 60°C for 18-20 h. After the reaction, the hot mixture was filtered and recrystallized from acetone to obtain 2,5-diiodobis(4-fluorobenzyloxy)benzene, the structure of which is shown below: ; (2) 1 eq of 2,5-diiodobis(4-fluorobenzyloxy)benzene, 4 eq of methyl 4-ethynylbenzoate, 0.3 eq of cuprous iodide, and 0.1 eq of bis(triphenylphosphine)palladium(II) dichloride were mixed, the mixture was degassed with nitrogen, anhydrous tetrahydrofuran and anhydrous triethylamine were added, and the mixture was stirred in the dark under a nitrogen atmosphere for 18 to 20 h. After the reaction was completed, the mixture was cooled to room temperature and poured into water. The mixture was purified by silica gel column chromatography to obtain 2,5-bis(4-fluorobenzyloxy)-1,4-bis(4-methylphenylethynyl)benzene, the structure of which is shown below: ; (3) 1 eq of 2,5-bis(4-fluorobenzyloxy)-1,4-bis(4-methylphenylethynyl)benzene was dissolved in 15 mL of tetrahydrofuran, 250 eq of potassium hydroxide was dissolved in 8 mL of methanol and added to the mixed solution, and stirred at room temperature for 20-22 h. The reaction mixture was acidified with 120 mL of 2 mol / L trifluoroacetic acid tetrahydrofuran solution, stirred at room temperature for 1 h, and then poured into water. The precipitate was filtered and washed with water. The crude product was treated with boiling water and ultrasonically shaken to remove inorganic salt impurities. The solid was dried and recrystallized in chloroform to obtain fluorine-containing pentaphenyl alkynyl dicarboxylic acid compound 1, the structure of which is shown below: ; Fluorine-containing pentaphenyl alkynyl dicarboxylic acid compound 2: homemade. The preparation method is similar to that of fluorine-containing pentaphenyl alkynyl dicarboxylic acid compound 1, except that 4-fluorobenzyl bromide in step (1) is replaced with benzyl bromide. Other conditions remain unchanged, resulting in fluorine-containing pentaphenyl alkynyl dicarboxylic acid compound 2, the structure of which is shown below: ; Dicarboxylic acid compound 3: pimelic acid, product number 1016832, purchased from Shanghai Haohong Biopharmaceutical Technology Co., Ltd.; Commercially available cellulose: Nanocellulose aqueous suspension, mass fraction of 1%, diameter: 15-25 nm, product number JLC12335, purchased from Jingkang Bioengineering Co., Ltd.
[0023] Cross-linking agent: trimethylolpropane triglycidyl ether, product number T856506, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; Plasticizer: dipropylene glycol dibenzoate, product number 1028018, purchased from Shanghai Haohong Biopharmaceutical Technology Co., Ltd.; Silicone defoamer: BYK-028, purchased from Guangzhou Qianguang Trading Co., Ltd. Surfactant: sodium lauryl sulfate, product number S850167, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; Propynyl glycidyl ether: product number 1269676, purchased from Shanghai Haohong Biopharmaceutical Technology Co., Ltd.; Sodium hypophosphite monohydrate: product number S822520, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; Triethylborane solution: 1 mol / L in hexane, product number T466127, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. Phosphorus pentoxide: Product No. P431841, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. 1-Bromopentane: Product No. B802255, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; 1-Bromohexadecane: product number 1017242, purchased from Shanghai Haohong Biopharmaceutical Technology Co., Ltd. 4-Fluorobenzyl bromide: Product No. SY001307, purchased from Shaoyuan Technology (Shanghai) Co., Ltd. 2,5-Diiodobenzene-1,4-diol: Product No. 1181381, purchased from Shanghai Haohong Biopharmaceutical Technology Co., Ltd.; 18-Crown-6-ether: product number 1023772, purchased from Shanghai Haohong Biopharmaceutical Technology Co., Ltd.; Methyl 4-ethynylbenzoate: product number 1028851, purchased from Shanghai Haohong Biopharmaceutical Technology Co., Ltd. Cuprous iodide: Product No. C017283, purchased from Shanghai Ketuo Chemical Technology Co., Ltd. Bis(triphenylphosphine)palladium(II) dichloride: product number 1020950, purchased from Shanghai Haohong Biopharmaceutical Technology Co., Ltd. 1-Aminomethylmaleimide hydrochloride: purchased from Nantong Wayendi Pharmaceutical Technology Co., Ltd. Grubbs second-generation catalyst: product number G810692, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; Meta-chloroperbenzoic acid: content 85%, purchased from Shanghai Myrrel Biochemical Technology Co., Ltd.; Disodium ethylenediaminetetraacetic acid solution: 50 g / L aqueous solution, product number E766637, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; Rosin resin: purchased from Chengdu Prolife Pharmaceuticals Research and Development Co., Ltd. VAE emulsion 1: glass transition temperature is -20℃, VAE920 emulsion from Wacker, Germany; VAE emulsion 2: glass transition temperature is 0℃, DA102VAE emulsion from Dalian Chemical, Taiwan, China.
[0024] Preparation Example Preparation Example 1 Modified cellulose-based emulsion 1: Homemade, the preparation method is as follows: (1) Preparation of modified cellulose 1 S1. Dissolve 2.5 eq of furan and 1 eq of 1-aminomethylmaleimide hydrochloride in toluene. Heat the mixture to 90°C and reflux for 20 h using a Dean-Stark apparatus. After the reaction, remove the solvent under reduced pressure. Purify the crude product by silica gel column chromatography to obtain the amino Diels-Alder addition product, whose structure is shown below: ; S2. Under a nitrogen atmosphere, 1.0 eq of the product from step S1 and 1.2 eq of epoxy hypophosphite compound 1 were dissolved and mixed in tetrahydrofuran, heated to 60°C, and stirred for 24 h. After the reaction, the solvent was removed by distillation under reduced pressure. The product was purified by silica gel column chromatography to obtain the hypophosphite-esterified amino Diels-Alder addition product, the structure of which is shown below: ; S3. 1.2 eq of fluorinated pentaphenyl alkynyl dicarboxylic acid compound 1 was dissolved in anhydrous dichloromethane, cooled to 0°C in an ice bath, and 1.2 eq of dicyclohexylcarbodiimide was added sequentially. The mixture was stirred for 10 min, followed by 0.1 eq of 4-dimethylaminopyridine. Finally, 1 eq of a 0.1 mol / L solution of the amino Diels-Alder addition product of hypophosphite in anhydrous dichloromethane was added dropwise. The ice bath was removed, and the mixture was stirred at room temperature for 20 h. After the reaction was completed, the mixture was filtered, and the filtrate was washed sequentially with a 5% (mass fraction) aqueous solution of citric acid, a saturated sodium bicarbonate solution, and brine, and then dried over anhydrous sodium sulfate. The hypophosphite monomer was obtained by silica gel column chromatography. The structure is shown below: ; S4. Synthesis of polyphosphite: Under nitrogen atmosphere, 1 eq of the phosphite monomer obtained in step S3 and 1 / 50 eq of the catalyst were dissolved in toluene and subjected to ring-opening metathesis polymerization. The reaction was heated to 70°C for 4 h, and then ethyl vinyl ether was added to quench the reaction. The solvent was removed, and the polyphosphite was recrystallized from acetone. S5. Epoxidation of polyphosphite: Under a nitrogen atmosphere, the polyphosphite obtained in step S4 was dissolved in toluene, m-chloroperbenzoic acid was added and stirred at 20°C for 4 h, and excess methanol was added to precipitate the epoxidized polyphosphite; S6. Cellulose modification: The nanocellulose aqueous suspension was diluted to a solution with a solid content of 0.5% by weight, and a 0.5 mol / L MgCl2 aqueous solution was added relative to 1.2 eq of nanocellulose, and stirred at room temperature for 30 min; epoxidized polyphosphite was added, and the mass ratio of nanocellulose solid content to epoxidized polyphosphite was 6:1. After stirring at 800 rpm at 30°C for 12 h, ultrasonic dispersion was continued for 30 min, and disodium ethylenediaminetetraacetic acid solution was added and stirred for 20 min; after standing at room temperature to remove bubbles, the solution was placed in liquid nitrogen and frozen for 10 min. The frozen sample was placed in a freeze dryer at a temperature of -50°C and a pressure of 20 Pa and freeze-dried for 60 h to obtain a gel-like solid. The obtained gel was placed in a vacuum drying oven at a temperature of 110°C for 10 min to obtain modified cellulose 1.
[0025] (2) Modified cellulose-based emulsion 1: Cellulose and modified cellulose 1 were mixed in a mixed solvent of water:NMP with a volume ratio of 7:3 at a mass ratio of 4.5:1, heated to 65 °C, stirred at 1200 rpm, and dissolved under ultrasonic-assisted treatment for 30 min to obtain modified cellulose-based emulsion 1; Preparation Example 2 Modified cellulose-based emulsion 2: homemade. The preparation method is similar to that of modified cellulose-based emulsion 1, except that the mass ratio of nanocellulose solid content to epoxidized polyphosphite in step (1) S6 is replaced with 3:1, while other conditions remain unchanged, thereby obtaining modified cellulose-based emulsion 2.
[0026] Preparation Example 3 Modified cellulose-based emulsion 3: homemade. The preparation method is similar to that of modified cellulose-based emulsion 1, except that the mass ratio of nanocellulose solid content to epoxidized polyphosphite in step (1) S6 is replaced with 9:1, while other conditions remain unchanged, thereby obtaining modified cellulose-based emulsion 3.
[0027] Preparation Example 4 Modified cellulose-based emulsion 4: homemade. The preparation method is similar to that of modified cellulose-based emulsion 1, except that the epoxy hypophosphite compound 1 in step (1) S2 is replaced by the epoxy hypophosphite compound 2. Other conditions remain unchanged, and modified cellulose 4 is obtained.
[0028] Preparation Example 5 Modified cellulose-based emulsion 5: homemade. The preparation method is similar to that of modified cellulose-based emulsion 1, except that the epoxy hypophosphite compound 1 in step (1) S2 is replaced by the epoxy compound 3. Other conditions remain unchanged, thus obtaining modified cellulose-based emulsion 5.
[0029] Preparation Example 6 Modified cellulose-based emulsion 6: homemade. The preparation method is similar to that of modified cellulose-based emulsion 1, except that the fluorinated pentaphenyl alkynyl dicarboxylic acid compound 1 in step (1) S3 is replaced by the fluorinated pentaphenyl alkynyl dicarboxylic acid compound 2. Other conditions remain unchanged, and modified cellulose-based emulsion 6 is obtained.
[0030] Preparation Example 7 Modified cellulose-based emulsion 7: homemade. The preparation method is similar to that of modified cellulose-based emulsion 1, except that the fluorine-containing pentaphenyl alkynyl dicarboxylic acid compound 1 in step (1) S3 is replaced by dicarboxylic acid compound 3. Other conditions remain unchanged, thereby obtaining modified cellulose-based emulsion 7.
[0031] Preparation Example 8 Modified cellulose-based emulsion 8: homemade. The preparation method is similar to that of modified cellulose-based emulsion 1, except that in step (2), the ratio of cellulose to modified cellulose 1 is replaced with 1:1, while other conditions remain unchanged, thereby obtaining modified cellulose-based emulsion 8.
[0032] Preparation Example 9 Modified cellulose-based emulsion 9: homemade. The preparation method is similar to that of modified cellulose-based emulsion 1, except that in step (2), the ratio of cellulose to modified cellulose 1 is replaced with 9:1, while other conditions remain unchanged, thereby obtaining modified cellulose-based emulsion 9.
[0033] Preparation Example 10 Modified cellulose-based emulsion 10: homemade. The preparation method is similar to that of modified cellulose-based emulsion 1, except that modified cellulose 1 is replaced with commercially available cellulose. Other conditions remain unchanged, resulting in modified cellulose-based emulsion 10.
[0034] Examples and Comparative Examples Examples 1 to 11 and Comparative Examples Modified cellulose adhesives 1-11: homemade, the preparation method is as follows: (1) Preparation of rosin water emulsion: solid rosin resin is added to boiling water, surfactant is gradually added, stirred at 800 rpm for 20 min, cooled to 60°C to obtain rosin water emulsion, and passed through a 200 mesh sieve to remove undispersed particles; the mass ratio of rosin to water is 1:6; the mass ratio of rosin to surfactant is 13:1; the surfactant is an anionic surfactant, preferably sodium lauryl sulfate; (2) Preparation of VAE composite emulsion: two VAE emulsions were mixed at 40 °C, 0.3% of silicone defoamer was added, and the mixture was stirred at 200 rpm for 15 min to obtain a VAE composite emulsion; (3) Cross-linking agent and plasticizer treatment: dilute the cross-linking agent with an equal volume of ethanol; preheat the plasticizer to 50°C; (4) Preparation of modified cellulose adhesive: The reactor was preheated to 45°C in a dark environment, and modified cellulose-based emulsions 1 to 10 and VAE composite emulsion were added and stirred in a gradient manner for 10 min. Then, rosin water emulsion was added and stirred for 5 min. The pretreated plasticizer was slowly added within 5 min. The diluted cross-linking agent was slowly added dropwise within 10 min. The temperature was maintained at 45°C, and the mixture was stirred at 150 rpm for 10 min. Vacuum degassing was performed for 20 min. The pH was adjusted to 7 with ammonia water, and the mixture was filtered through 0.5 μm precision to obtain modified cellulose adhesives 1 to 11 and the comparative example.
[0035] Table 1 Modified cellulose adhesive formulations of Examples 1 to 11 and comparative examples (by weight)
[0036] The following are the test methods for the performance parameters involved in the present invention: 1. Bond strength test: Tested according to JC / T438-2019 standard, using a WDT electronic universal material testing machine; 2. Water resistance test: After the adhesive is coated under the same conditions, soak it in 25℃ water for 24 hours, observe its swelling and record the water immersion strength retention rate (%); Table 2 Test results of adhesive properties of Examples 1 to 11 and comparative examples
[0037] It can be seen from the data in Table 2 that in Examples 1 to 3, the proportion of modified cellulose in Example 2 is reduced, and the bonding strength is reduced relative to that in Example 1, while the proportion of modified cellulose in Example 3 is increased, and the bonding strength is increased due to the high filler; the modified cellulose 2 in Example 4 has good water resistance due to its high polyphosphite content, but the relative proportion of cellulose is reduced, and the strength is slightly lower than that in Example 1; the modified cellulose 3 in Example 5 has relatively reduced water resistance and strength due to its high cellulose proportion; the modified cellulose 4 in Example 6 adopts a short chain structure, and both the bonding strength and water resistance are reduced; the modified cellulose 5 in Example 7 does not contain phosphorus, and both the bonding strength and water resistance are reduced; the modified cellulose 6 in Example 8 does not contain fluorine groups, and its water resistance and bonding strength are reduced relative to that in Example 1; Example 9 uses a flexible chain of pimelic acid to replace the rigid structure of the benzene ring and alkynyl group, and its water resistance and bonding strength are reduced; the comparative example uses commercially available cellulose without modification, and has the worst performance.
[0038] In summary, the fluorine-containing alkynyl conjugated system enhances the van der Waals force through the electron cloud, the long-chain alkanes prevent water molecules from penetrating the interface through the hydrophobic barrier, and the phosphate groups form multiple hydrogen bonds with the hydroxyl groups of cellulose, thereby enhancing the bonding strength and water resistance of the modified cellulose adhesive in many aspects and achieving targeted performance improvement through molecular design.
[0039] The preferred embodiments of the present invention disclosed above are intended only to help illustrate the present invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the present invention to the specific embodiments described. Obviously, many modifications and variations are possible based on the content of this specification. These embodiments are selected and described in detail in this specification to better explain the principles and practical applications of the present invention, thereby enabling those skilled in the art to better understand and utilize the present invention. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A modified cellulose adhesive, characterized in that The invention comprises the following components in parts by weight: 50-70 parts of a modified cellulose-based emulsion, 10-20 parts of a VAE composite emulsion, 5-8 parts of a rosin water emulsion, 3-8 parts of a cross-linking agent, and 2-5 parts of a plasticizer; the modified cellulose-based emulsion is obtained by mixing cellulose and modified cellulose in proportion; the modified cellulose is obtained by grafting a nanocellulose solution with an epoxy hypophosphite compound and a fluorine-containing pentaphenyl alkynyl dicarboxylic acid compound; the structure of the modified cellulose is shown in Formula 1: , formula 1.
2. The modified cellulose adhesive according to claim 1, wherein The preparation method of the modified cellulose comprises the following steps: S1. Dissolve furan and 1-aminomethylmaleimide hydrochloride in toluene and reflux using a Dean-Stark apparatus to obtain an amino Diels-Alder addition product; S2. Under a nitrogen atmosphere, the product of step S1 and the epoxy phosphite compound were dissolved and mixed in tetrahydrofuran, and heated with stirring to obtain a hypophosphite-esterified amino Diels-Alder addition product; S3. The fluorine-containing pentaphenyl alkynyl dicarboxylic acid compound was dissolved in anhydrous dichloromethane and cooled to 0°C in an ice bath. Dicyclohexylcarbodiimide and 4-dimethylaminopyridine were added sequentially, and a 0.1 mol / L solution of the amino Diels-Alder addition product of hypophosphite esterified in anhydrous dichloromethane was added dropwise. The ice bath was removed and the reaction was stirred at room temperature to obtain a hypophosphite monomer. S4. Synthesis of polyphosphite: Under a nitrogen atmosphere, the phosphite monomer obtained in step S3 and the catalyst were dissolved in toluene, and ring-opening metathesis polymerization was performed. After the temperature was raised, vinyl ethyl ether was added to quench the reaction, and the polyphosphite was obtained by recrystallization from acetone; S5. Epoxidation of polyphosphite: Under a nitrogen atmosphere, the polyphosphate obtained in step S4 was dissolved in toluene, m-chloroperbenzoic acid was added and the reaction was stirred, and excess methanol was added to precipitate the epoxidized polyphosphite; S6. Cellulose modification: Dilute the nanocellulose aqueous suspension to a solution with a solid content of 0.4% to 0.8% by weight, add an aqueous MgCl2 solution, and stir at room temperature; add epoxidized polyphosphite, stir, continue ultrasonic dispersion, add disodium ethylenediaminetetraacetic acid solution, and stir; let stand at room temperature to remove bubbles, then freeze-dry to obtain a gel-like solid, and vacuum dry to obtain phosphite-modified cellulose.
3. The modified cellulose adhesive according to claim 2, wherein The catalyst in step S4 is one or more of Grubbs first generation catalyst, Grubbs second generation catalyst, and Grubbs third generation catalyst.
4. The modified cellulose adhesive according to claim 1, wherein The structural formula 2 of the fluorine-containing pentaphenyl alkynyl dicarboxylic acid compound is shown as follows: , formula 2.
5. The modified cellulose adhesive according to claim 1, wherein The structure of the epoxy phosphinate compound is shown in Formula 3: , formula 3.
6. The modified cellulose adhesive according to claim 1, wherein The VAE composite emulsion is composed of two VAE emulsions with different glass transition temperatures, wherein the glass transition temperature of one VAE emulsion is lower than 0°C, and the glass transition temperature of the other VAE emulsion is higher than or equal to 0°C, and the mass ratio of the two emulsions is (0.45-0.55):(0.45-0.55); the crosslinking agent is trimethylolpropane triglycidyl ether; and the plasticizer is dipropylene glycol dibenzoate.
7. The modified cellulose adhesive according to claim 1, wherein The mass ratio of the cellulose to the modified cellulose is (1-8):
1.
8. The method for preparing the modified cellulose adhesive according to any one of claims 1 to 7, wherein: The following steps are involved: (1) Preparation of modified cellulose-based emulsion: cellulose and modified cellulose are mixed in a mixed solvent, heated and stirred, and ultrasonically assisted dissolution; (2) Preparation of rosin water emulsion: solid rosin resin is added to boiling water, surfactant is gradually added, and the mixture is stirred and cooled to obtain rosin water emulsion; (3) Preparation of VAE composite emulsion: two VAE emulsions were mixed at 40°C, silicone defoamer was added, and the mixture was stirred to obtain VAE composite emulsion; (4) Cross-linking agent and plasticizer treatment: dilute the cross-linking agent with an equal volume of ethanol; preheat the plasticizer to 50°C; (5) Preparation of modified cellulose adhesive: preheat the reactor in a dark environment, add the modified cellulose-based emulsion and VAE composite emulsion and stir them in a gradient manner, then add the rosin water emulsion and stir, slowly add the pretreated plasticizer, and then slowly add the diluted cross-linking agent dropwise, maintain the temperature at 45°C, stir, vacuum degas, adjust the pH to 7, and finely filter to obtain the modified cellulose adhesive.
9. The method for preparing the modified cellulose adhesive according to claim 8, wherein: The mixed solvent in step (1) is a mixed solvent with a volume ratio of water to NMP of 7:3; the ultrasonic auxiliary parameters are set to 40 kHz and 600 W.
10. The method for preparing the modified cellulose adhesive according to claim 8, wherein: The gradient stirring in step (5) is as follows: the stirring speed is 80 rpm for 0-2 min, the stirring speed is 120 rpm for 3-5 min, and the stirring speed is 150 rpm for 6-10 min.
Citation Information
Patent Citations
Environmentally-friendly aqueous binder
CN105176457A
Emulsion for improving rheological stability and preparation method and application thereof
CN116751543A
Cited By
Cellulose antibacterial coating and preparation method thereof
CN120795688A
